The role of elective surgery following acute colonic diverticulitis - Machado, Catarina Tavares (2017)
The surgical treatment following acute diverticulitis (DV) has been an ongoing subject of debate. During the first half of the 20th century, only complicated cases of acute DV were surgically treated. During the second half, some studies suggested that patients with recurrent episodes of uncomplicated DV had an increased risk of complicated disease, morbidity, and mortality, and, for that reason, surgery was indicated also for these patients. In 1995, the ASCRS recommended elective bowel resection after two episodes of uncomplicated acute DV (or one episode for patients younger than 50), or after one episode of complicated DV. Recent studies have questioned these three recommendations. First, although acute DV is particularly aggressive during its first episode, subsequent episodes tend to be significantly more benign and successfully manageable with non-operative treatment. Elective surgery decreases neither the likelihood of emergency surgery nor the overall mortality due to DV complications. Moreover, elective surgery is not risk free, and some patients still experience acute DV episodes post-operatively. Second, in patients under 50, the disease does not seem to be as aggressive as previously implied. The response to medical treatment and post-operative morbidity and mortality remain similar to older patients. Third, regarding episodes of complicated DV, whether surgery is always necessary after successful percutaneous abscess drainage has also been a matter of debate. International guidelines are consensual when indicating precocious surgical resection for patients chronically immunosuppressed, who have collagen-vascular disease, or chronic renal disease. While waiting for the results of the first randomised clinical trials comparing different treatment strategies for acute DV, the present paper reviews the debate regarding the indications for elective surgery.